Monitoring Arctic Ocean Hydrography Using Autonomous Underwater Vehicles - Bellingham, James G. (1998)
Recent observations in the Arctic Ocean indicate that it is undergoing substantial change on a basin scale. Our project goal is to develop Autonomous Underwater Vehicles (AUVs) capable of observing basin scale evolution in the Arctic. This requires the development of energy, navigation and communication systems specifically tailored for extended autonomous operations under ice. We will provide a means of monitoring changes taking place in the Arctic Ocean and investigate its impact on global warming. Such a capability is of national and global interest and importance. See also ADM002252. The original document contains color images.